Effects of Marketing Mix on Students’ Selection of Transnational Top-up Degrees in Hong Kong - Lau, May Yee Melissa (International Review of Management and Marketing, 2020)
With fierce competition in transnational higher education (TNHE), marketing mix strategies should be adopted to attract students to study the transnational top-up degrees offered in Hong Kong. This research investigates the effects of service marketing mix on students’ selection of transnational top-up degrees offered in Hong Kong. Understanding the perceptions of Hong Kong students can help institutions make informed decisions on what is important to students when delivering TNHE in Hong Kong. Institutions can formulate strategic plans and allocate appropriate resources to solicit right partners and recruit target students. Quantitative and qualitative methods were adopted in this research. The results reveal ‘Qualifications are recognized in Hong Kong’ is the most important factor that influences students’ selection of transnational top-up degrees offered in Hong Kong. Recommendations are made for senior management of TNHE to design effective marketing mix strategies in Hong Kong. Keywords: 7Ps Marketing Mix, Marketing Strategy, Student Selection, Top-up Degree, Higher Education, Program Development JEL Classifications: M31; I21 DOI: https://doi.org/10.32479/irmm.10163